Clinical Study on a Case of Axonotmesis of Common Peroneal Mononeuropathy by using 3 times EMG Studies - Seong-Gyu Cho; Byung-Shik Chung; Hyung-Seok Yun; Joo-Hyung Lee; Sang-Hoon Lee; Dong-Min Seo; Jae-Dong Lee (Korean Pharmacopuncture Institute, 2001)
In Oriental Medicine, mononeuropathy belongs to or . Common peroneal neuropathy(CPN) is the most frequently encountered mononeuropathy in the lower extremity. It is usually caused by direct surgery injury, compression, leg crossing, trauma, traction etc, occasionally by nerve tumor. A 47-year-old healthy man was complained of the sudden development of left foot drop and sensory manifestation owing to suspected compression and habitual leg-crossing. Acupuncture along with bee-venom acupuncture, moxibustion was performed mainly at Stomach and Gallbladder Meridian specially ST36, ST37, ST40, GB34 and GB39. Nerve conduction study and electromyography was also performed three times. Symtoms was relieved fast, and full recovery took about 110 days. Acupuncture and bee-venom acupuncture are considered to be beneficial to CPN. More clinical trials and studies are needed.